Collaborative Governance in the Implementation of E-Government-Based Public Services Inclusion in Jambi Province, Indonesia - Rio Yusri Maulana (Journal of Governance, 2020)
The Open Government Indonesia (OGI) action plan, provides a focus on strengthening public services and strengthening public information disclosure, as well as strengthening data governance, it can be facilitated by the presence of government base applications. The success in implementing e-government is the level of policy, fiscal support, and infrastructure. At the community level, although the implementation of e-government has opened up a large space for community participation in using civil rights through a variety of available channels, limited access is a major technical obstacle, supported by a lack of socialization, and application design that is not user-friendly. Initial findings explain that the collaborative process seems less-coordination, open government design has not been connected to the rules for implementing innovations in the regional government, the cause is the absence of commitment from regional heads and stakeholders, the gap between understanding and practical facts is still too wide.